SACROSANCTUM CONCILIUM: Exploring the Underlying Theological Principles of the Conciliar Constitution on Sacred Liturgy - Lionel, S. Joseph (Asian Horizons, 2013)
The Conciliar document on Sacred Liturgy is called simply Constitution on the Sacred Liturgy. It is not termed as dogmatic constitution or decree. It is a permanent law and not a mere decree settling some momentary questions. The liturgical Constitution of the Second Vatican Council is disciplinary and not dogmatic. That is, it contains dispositions pertaining to the sphere of practical life rather than dogmatic teachings. However, these dispositions are firmly grounded in the teachings of the Church. The teachings are taught in the liturgical constitution but not defined. In other words, the liturgical constitution has the character statements of the magisterium ordinarium.